Draft Annual Plan 1971-72 Government of Assam - Planning Commission (Planning Commission, 1971)
In the North Eastern region of India, Assam State standing like a sentinel guard on the north-eastern frontier of the country, being flanked on three sides by the foreign territories, It is linked with the rest of the country by a narrow strip of land through North Bengal, Assam forms the core of the strategic northeastern region of India comprising Assam, NEFA, Nagaland Manipur and Tripura and as such serves as the focal point of the communication lines to these outlying areas.
Government of Assam, Planning and Development Department